60. Defective interhemispheric inhibition in focal epilepsies. Issue 12 (December 2016) - Strigaro, G.; Matino, E.; Pizzamiglio, C.; Tondo, G.; Falletta, L.; Barbero, P.; Varrasi, C.; Cantello, R.
Abstract : Focal epilepsies (FEs) arise from a lateralized network. In generalized epilepsies (GEs) there is a bilateral network involvement from the outset. The corpus callosum is the anatomical substrate for interhemispheric spread, although its detailed physiological role is uncertain. We used transcranial magnetic stimulation (TMS) to explore the physiology of the corpus callosum in patients with FE and idiopathic GE (IGE), as compared to healthy subjects (HS). We studied 16 patients with FE, 17 with IGE, and 17 HS of similar age and sex. We used TMS to measure the interhemispheric inhibition (IHI) from left-to-right primary motor cortex (M1) and viceversa. A conditioning stimulus (CS) was given to one M1 10 and 50 ms before a test stimulus delivered to the contralateral M1. Statistics was based on ANOVAs. Across HS, IHI was reproducible, since a contralateral CS suppressed MEPs at ISIs of 10 and 50 ms ( p  < 0.05). Similar effects occurred in IGE patients ( p  < 0.05). FE patients behaved differently, since IHI was significantly ( p  < 0.05) reduced bilaterally. In conclusion, FE patients had a bilateral defective inhibitory response. We suggest that it may represent one key factor for the contralateral spread of focal discharges, and seizure generalization.